2010
DOI: 10.1159/000321070
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Spectrum Disorders in Obsessive-Compulsive Disorder and Other Anxiety Disorders

Abstract: Background: There has been debate about whether obsessive-compulsive disorder (OCD) should be classified as one of the anxiety disorders, or should rather be categorized with obsessive-compulsive spectrum conditions. Sampling and Methods: The question of where OCD should be located in the diagnostic system was addressed by investigating the relationship of OCD, obsessive-compulsive spectrum disorders (OCSDs), and anxiety disorders. We administered a structured diagnostic interview (the SCID-OCSD) for assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 120 publications
3
21
0
1
Order By: Relevance
“…In addition, these disorders and OCD share similarities in response to treatment as well [10,11]. In one of the largest studies conducted to-date, Stein and Lochner [12] assessed 417 patients with a diagnosis of classic OCD, for co-existence of other OCSDs. They also compared the results with patient populations with panic disorder and social anxiety disorder (based on the above mentioned hypothesis that OCDs share common features with anxiety disorders also).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these disorders and OCD share similarities in response to treatment as well [10,11]. In one of the largest studies conducted to-date, Stein and Lochner [12] assessed 417 patients with a diagnosis of classic OCD, for co-existence of other OCSDs. They also compared the results with patient populations with panic disorder and social anxiety disorder (based on the above mentioned hypothesis that OCDs share common features with anxiety disorders also).…”
Section: Discussionmentioning
confidence: 99%
“…It is being thought that severe military conflicts in Africa shorten the expected lifetime for more than 2 years. In general, WHO had calculated that 269 thousand people had died in 1999 due to the effect of wars and that loss of 8.44 million healthy years of life had occurred (2,3). Wars negatively affect the provision of health services.…”
Section: War and Women's Healthmentioning
confidence: 99%
“…Moreover, the wars cause the migration of qualified health employees, and thus the health services hitches. Assessments made indicate that the effect of destruction in the infrastructure of health continues for 5-10 years even after the finalization of conflicts (3). Due to resource requirements in the restructuring investments after war, the share allocated to health has decreased (1).…”
Section: War and Women's Healthmentioning
confidence: 99%
“…Anthony and Hollander (1993) postulated that hypersexual behavior was part of an obsessive-compulsive spectrum disorder (OCSD). In a recent study, Lochner and Stein (2010) administered a structured diagnostic interview for OCSD (SCID-OCSD) and reported that HD was more common in OCSD.…”
mentioning
confidence: 99%